Technology adoption of small and medium-sized enterprises and performance in European countries: A cross-country panel cointegration analysis - Endrődi-Kovács, Viktória; Pérez Garrido, Betsabé; Sebrek, Szabolcs Szilárd (Entrepreneurial Business and Economics Review, 2024)
Objective: The objective of the article is to explore the impact of the new technology adoption on the performance of small and medium-sized enterprises (SMEs) at the country level. Research Design & Methods: The authors modelled the effect of technology adoption (TA) on SMEs’ market and sustainability performance by using the dynamic ordinary least squares regression technique. The analysis used a sample of 12 EU countries from 2008 to 2021. Regional specificities of the Baltic and Central European countries were introduced. We obtained a novel database from the European Union’s SME Performance Review indicators. Findings: The results show that TA positively affects both market and sustainability performance in European SMEs at the country level. This impact is larger for market performance than for sustainability performance. Moreover, the long-run equilibrium relationships between TA and market performance demonstrate a positive effect in Central European countries and a negative effect in Baltic countries. Moreover, the impact of TA on sustainability performance proves negative for the joint group of new member countries consisting of Baltic and Central European states unlike for old member countries. Implications & Recommendations: The findings suggest the adoption of a more strategic perspective among SMEs regarding TA. Furthermore, the study offers policy recommendations aimed at facilitating the green transformation of new member countries. Contribution & Value Added: The effects of TA on market and sustainability performance have not yet been examined by applying an econometrically sophisticated analytical sequence on a panel dataset of countries’ SMEs. For policymakers, the findings demonstrate that environmentally friendly technologies, through enhancing sustainability performance, can be a solid pillar that undergirds a widespread green economic transition.